A COMMON FIXED POINT THEOREM FOR UNIQUE RANDOM POINT IN HILBERT SPACE USING SIX RANDOM OPERATORS - Geeta Modi, Ram Naresh Gupta (International Journal of Research Science and Management, 2015)
The aim of this paper is to obtain a common fixed point theorem for six random operators by using weak compatibility, semicompatibility in the non- empty closed subset of a separable Hilbert Space. Our results generalize and extend the result.